2002
DOI: 10.1046/j.0106-9543.2002.01647.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA and cytokine gene polymorphisms in biliary atresia

Abstract: Overall there were no statistically significant differences in the distribution of any of the genes tested comparing patients and controls. These data suggest that biliary atresia is not an HLA-associated disease and that polymorphisms in both the interleukin-1 and interleukin-10 genes are not risk factors for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Studies of a possible link between HLA type and BA have yielded conflicting results. [30][31][32] Because of the rarity of BA (approximately 1:8,000-18,000 live births) 33 and the paucity of liver and bile duct tissue available for research, the use of murine models provides valuable insight into the potential mechanisms of bile duct injury in this devastating disease. In this study, we show that the progressive bile duct injury is attributable in part to bile duct epithelia-specific T cell-mediated autoimmunity and that serum autoantibodies reactive to bile duct epithelial proteins are present in murine BA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of a possible link between HLA type and BA have yielded conflicting results. [30][31][32] Because of the rarity of BA (approximately 1:8,000-18,000 live births) 33 and the paucity of liver and bile duct tissue available for research, the use of murine models provides valuable insight into the potential mechanisms of bile duct injury in this devastating disease. In this study, we show that the progressive bile duct injury is attributable in part to bile duct epithelia-specific T cell-mediated autoimmunity and that serum autoantibodies reactive to bile duct epithelial proteins are present in murine BA.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, DNA genotyping has been adapted for HLA typing, yielding a greater number of HLA loci and alleles to be tested with much greater accuracy. Using DNA genotyping, Donaldson et al (67) found no HLA associations in 101 BA patients from the United Kingdom. It is clear that a large, multicentered study of HLA genotyping (including high resolution of HLA-class II) and a sample size calculated to generate statistically sound results is needed.…”
Section: T-cell-mediated Inflammation T-cell Activation Requires Thementioning
confidence: 99%
“…Several candidate-gene association studies have been conducted thus far on genes selected mainly for their role in inflammatory, immune and autoimmune responses and gene-expression analyses (12)(13)(14)(15). Indeed, gene-expression analyses on bile duct or liver tissues of mice and humans indicated that genes involved immune and autoimmune response may play a role in BA development (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%